[OP.3B.02] CORRELATION BETWEEN BLOOD LEVELS OF S100B PROTEIN AND INCIDENCE OF HEART FAILURE OR IMA IN A CARDIOLOGY UNIT. (September 2017) - Quartuccio, S.; Imbalzano, E.; Trapani, G.; Lizio, G.; Di Salvo, E.; Casciaro, M.; Gangemi, S.
Abstract : Objective: Chronic heart failure is one of the most common consequence of myocardial infarction, and is characterized by a reduction of the heart ability to face peripheral blood distribution. Chronic heart failure (HF) and myocardial infarction (IMA) are often associated to the augmentation of inflammation markers. S100B is an alarmin secreted by damaged cardiomyocites. Serum S100B levels were increased in the pathogenesis of heart disease and involved their pathogenetic mechanisms. S100B is a tissue-specific protein (chondrocytes, adipocytes, skeletal myofibers, cardiomyocytes, dendritic cells, etc.); it was largely demonstrated to be released after a damage and the consequent remodelling involving cardiac tissue. We examined the correlation between S100B protein serum levels and the incidence of acute heart failure and IMA in symptomatic patients. Figure. No caption available. Design and method: We conducted a prospective study on 90 patients aged between 50 and 72 years accepted to our Unit referring cardiac associated symptoms (thorax pain, dyspnea, arrhythmic symptoms). They were divided in three groups: healthy subjects (group A), chronic heart failure patients (group B) and IMA patients (group C). CRP, NT-proBNP, and routine exam were performed in every patient. Moreover it was made a S100B dosage was made. Results: Results demonstrated different levels among healthy subjects. However in chronic heart failure patients the alarmin levels were higher but not significantly augmented. Instead AMI patients had mean values of S100B doubled than the other two groups and significantly augmented. Conclusions: According to our data S100B as the potential to be, in a near future, be considered as an acute myocardial infaction marker in addiction to the ones existing. However more studies are needed to identify possible byas elements in S100B serum dosage. This together with other elements are guiding us to a better understand of micro-structural changes in damaged heart in order to consider new therapeutic targets.